Novel Opioids: Systematic Web Crawling Within the e-Psychonauts’ Scenario - Arillotta, Davide; Schifano, Fabrizio; Napoletano, Flavia; Zangani, Caroline; Gilgar, Liam; Guirguis, Amira; Corkery, John Martin; Aguglia, Eugenio; Vento, Alessandro (Frontiers in Neuroscience, 2020)
BACKGROUND. A wide range of novel psychoactive substances (NPS) is regularly searched and discussed online by e-psychonauts. Among NPS, the range of prescription/non-prescription opioids (fentanyl and non-fentanyl analogues) and herbal derivatives currently represent a challenge for governments and clinicians. METHODS. Using a web crawler (i.e. NPS.Finder®) the present study aimed at assessing psychonaut fora/platforms to better understand the online situation regarding opioid molecules. RESULTS. The open-web crawling/navigating software identified some 426 opioids, including 234 fentanyl analogues. Of these, 176 molecules (162 were very potent fentanyls, including 2 ohmefentanil and 7 carfentanil analogues) were not listed in either international or European NPS databases. CONCLUSIONS. A web crawling approach helped in identifying a large number, indeed higher than that listed by European/international agencies, of unknown opioids likely to possess a significant misuse potential. Most of these novel/emerging molecules are still relatively unknown. This is a reason of concern; each of these analogues potentially present with different toxicodynamic profiles and there is a lack of docking, preclinical, and clinical observations. Strengthening multidisciplinary collaboration between clinicians and bioinformatics may prove useful in better assessing public health risks associated with opioids.